O preconceito em face da diversidade de gênero na escola - Viegas, Vivian Paula (2021)
Approaching the theme of diversity and gender at school is still a great challenge fraught with prejudice, doubts and fears. This study investigated teachers’ and students’ views towards this theme of diversity, reflecting on conventionality, aggression , authoritarianism, sexuality and superstitious and stereotyped forms of thinking. Such endeavor was designed to analyze trends in attitudes that may express prejudice towards women and the LGBTQIA+ community. These tendencies were found based on teachers’ and students’ statements on gender in elementary school in the town district of Diadema and Sao Paulo. The initial hypothesis for this research was formulated as follows: even though the school is a privileged place to work the ethical values of respect for others, based on the recognition of plurality and in the need for inclusive and democratic social relations, most often we find the promotion of ideas and practices that reinforce stereotypes and perpetuate gender bias. The data were obtained using a Likert- type attitude scale , called Gender Prejudice (PG), developed and validated for this research. The reflections on gender were based on research by Butler, Junqueira, among other researchers. The theoretical contribution was extracted from the works of Adorno and Horkheimer, especially the considerations over the individual, society and prejudice